2017
DOI: 10.1186/s40168-017-0378-z
|View full text |Cite|
|
Sign up to set email alerts
|

The rumen microbiome as a reservoir of antimicrobial resistance and pathogenicity genes is directly affected by diet in beef cattle

Abstract: BackgroundThe emergence and spread of antimicrobial resistance is the most urgent current threat to human and animal health. An improved understanding of the abundance of antimicrobial resistance genes and genes associated with microbial colonisation and pathogenicity in the animal gut will have a major role in reducing the contribution of animal production to this problem. Here, the influence of diet on the ruminal resistome and abundance of pathogenicity genes was assessed in ruminal digesta samples taken fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
119
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(131 citation statements)
references
References 58 publications
7
119
5
Order By: Relevance
“…Similar to this study, tetracycline resistance was reported as highly abundant in the rumen, otherwise prevalence of resistance to other antibiotics varies between studies [36,37]. Although the methodologies used to detect ARGs could play a role in these differences [35][36][37], it is probable that variation in the rumen resistome may differ between countries and regions as it can reflect decades of exposure since antibiotics started to be used in farms.…”
Section: Antibiotic Resistance Genessupporting
confidence: 77%
See 2 more Smart Citations
“…Similar to this study, tetracycline resistance was reported as highly abundant in the rumen, otherwise prevalence of resistance to other antibiotics varies between studies [36,37]. Although the methodologies used to detect ARGs could play a role in these differences [35][36][37], it is probable that variation in the rumen resistome may differ between countries and regions as it can reflect decades of exposure since antibiotics started to be used in farms.…”
Section: Antibiotic Resistance Genessupporting
confidence: 77%
“…Information from ruminants is predominantly from the fecal microbiome [34], and although the importance of the rumen microbiome has also been highlighted [35,36], data on the rumen resistome is still fragmented. As an example of the useful information than can be retrieved from a gene catalog, we evaluated the presence of ARG in the rumen microbiome as previously reported [12].…”
Section: Antibiotic Resistance Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are some examples available in the literature. For instance, the role of the rumen as a reservoir of virulence‐associated genes has been monitored by (Singh et al., ) and (Auffret et al., ). The benefits (rapidity; simultaneous detection of a range of virulence genes; potential for obtaining information on the genetic background of the virulence determinants), limitations (results will depend on the quality of the databases; uncertainty on the agreement between virulence genes detection and phenotype), and opportunities (potential to re‐analyse previously sequenced genomes and to link sequencing data with metadata from the samples) of using shotgun metagenomics with this aim are similar to those previously described for the resistome.…”
Section: Assessmentmentioning
confidence: 99%
“…Fibrobacteres devote the highest percentage of their proteome to carbohydrate metabolism (over 6.6%), as is expected due to their fibre-attached, high cellulolytic activity. Only a few studies exist on the role of Planctomycetes in the rumen [52][53][54] , however whilst they contribute a relatively low number of proteins in our dataset (30172), just over 5% of those proteins are predicted to be CAZymes, suggesting a role in and adaptation to carbohydrate metabolism. Most phyla encode relatively similar proportions of each of the eight classes of CAZyme; however, the archaea encode proportionally more glycosyl transferases, and the Fibrobacteres encode proportionally more carbohydrate binding molecules.…”
Section: A Dataset Of Rumen Proteins For Functional and Proteomic Anamentioning
confidence: 93%